Fatores relevantes na determinação das escolhas gerenciais e organizativas dos fruticultores da região norte fluminense - de Souza, Paulo Marcelo; de Paulo, Robson Mendes; Ponciano, Niraldo José (Universidade Federal Rural do Rio de Janeiro, 2015)
The objective of the research was to characterize the social profile of the fruit farmers of the North region of the Rio de Janeiro state and to explain, with the use of the logit model, some of the decisions taken for these producers. To obtain the data, 378 fruit farmers were interviewed. The results show that level of education is one of the most important factors in the farmer decisions, concerning aspects a administration and organization. The importance of the fruit production and the experience with this activity are also important aspects.